1972
DOI: 10.2307/1540065
|View full text |Cite
|
Sign up to set email alerts
|

THE LIFE CYCLE OFPEACHIA QUINQUECAPITATA, AN ANEMONE PARASITIC ON MEDUSAE DURING ITS LARVAL DEVELOPMENT

Abstract: Pcachia. quinquecapitata McMurrich ( 1913 ) is a burrowing anemone of the family Haloclavidae found on the Pacific coast of North America.McMurrich described the adult /'. quinquecapitata and also indicated that a larval anemone parasitic on the hydromedusa Acqnorca probably belonged to this same species. However, since he could not raise one to the adult, non-parasitic stage, he placed it in the genus Bicidhtin. created by Agassiz (1859) for a parasite of a scyphozoan medusa on the Atlantic coast of North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Additional problems with the cnidarian interpretation of Olivooides include the stellate tissue seen in the embryonic and putative polyp stages, which has no equivalent in the periderm of coronate scyphozoan polyps, and the absence in Olivooides of the attachment structure seen in polyps of extant coronate scyphozoans. These could be reconciled as autapomorphies of Olivooides, though similar structures, comprising twisted clusters of actin filaments, occur in association with the egg cases of anthozoans [33,34].…”
Section: (C) Cnidarian Affinitymentioning
confidence: 97%
“…Additional problems with the cnidarian interpretation of Olivooides include the stellate tissue seen in the embryonic and putative polyp stages, which has no equivalent in the periderm of coronate scyphozoan polyps, and the absence in Olivooides of the attachment structure seen in polyps of extant coronate scyphozoans. These could be reconciled as autapomorphies of Olivooides, though similar structures, comprising twisted clusters of actin filaments, occur in association with the egg cases of anthozoans [33,34].…”
Section: (C) Cnidarian Affinitymentioning
confidence: 97%
“…Within all-female pools, spawning synchrony depended on the proximity of the nearest rockpool containing a spawning male, with pools that were close to spawning males having higher synchrony. For a range of invertebrates (and anemones in particular), sperm has been shown to induce spawning in females (Clark & Dewell 1974, Spaulding 1972, Sebens 1981, Pennington 1985, O'Connor & Heasman 1995. Sperm or some associated product may act as a spawning trigger in Oulactis mucosa, with the effectiveness of this trigger degrading with dilution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that reproduction by freespawning may therefore be problematic because of the large distances between males and females (Sebens 1981), but this remains to be tested. Second, many species of anemones spawn in response to the presence of sperm (Spaulding 1972, Clark & Dewell 1974, and it is thought that males signal females to spawn in this way. Given that anemones have been reported to spawn at low tide or during periods of emersion (Siebert 1974, Sebens 1981, Strathmann 1991, spawning synchrony may be relatively low because of a lack of communication between individuals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to E. lineata larvae of two species of the genus Peachia (the family Haloclavidae) infect hydro-and scyphomedusae (Spaulding 1972, McDermott et al 1982. Spaulding (1972) made a thorough investigation on the life cycle of Peachia quinquecapitata McMurrich infecting the hydromedusa Clytia gregaria (Agassiz) (as Phialidium gregarium) on the Pacific coast of North America.…”
Section: Anthozoansmentioning
confidence: 99%
“…Spaulding (1972) made a thorough investigation on the life cycle of Peachia quinquecapitata McMurrich infecting the hydromedusa Clytia gregaria (Agassiz) (as Phialidium gregarium) on the Pacific coast of North America. The life cycle differs from that of E. lineata, and is composed of two phases, the endoparasitic and ectoparasitic phases.…”
Section: Anthozoansmentioning
confidence: 99%